2022
DOI: 10.1111/cch.12952
|View full text |Cite
|
Sign up to set email alerts
|

Perceived impact of lockdown on daily life in children with physical disabilities and their families during the COVID‐19 pandemic

Abstract: Background The first lockdown during COVID‐19 pandemic in France led to an abrupt change in children's daily lives. For children with physical disabilities and their families, activities were limited, access to healthcare and therapy was disrupted, and family organization was altered. The objective was to report the impact of the lockdown on daily life activities and well‐being of children with physical disabilities as perceived by caregivers. Methods Two online national surveys were addressed to the parents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
0
25
0
4
Order By: Relevance
“…The pandemic has often resulted in decreased life satisfaction [ 10 ], increased internalising symptoms (including anxiety and depression), and more mental health problems and psychosomatic complaints [ 11 , 12 , 13 , 14 ]. However, there is a paucity of knowledge about the effects of the pandemic on children with chronic conditions, who are a population at risk of decreased mental wellbeing [ 15 , 16 ]. In general, children with a chronic condition rate their psychosocial functioning, developmental milestones, and mental wellbeing lower than their healthy peers [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has often resulted in decreased life satisfaction [ 10 ], increased internalising symptoms (including anxiety and depression), and more mental health problems and psychosomatic complaints [ 11 , 12 , 13 , 14 ]. However, there is a paucity of knowledge about the effects of the pandemic on children with chronic conditions, who are a population at risk of decreased mental wellbeing [ 15 , 16 ]. In general, children with a chronic condition rate their psychosocial functioning, developmental milestones, and mental wellbeing lower than their healthy peers [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the children’s abilities, behavior and the motor functioning were more affected during the pandemic. In accordance with this, different authors found a decrease in the general mood [ 13 ] or an increase in irritability, aggressiveness and anger [ 9 ] and, more generally, behavioral problems [ 5 , 10 , 12 ]. This was true also for children with other disabilities [ 20 ].…”
Section: Discussionmentioning
confidence: 56%
“…Varengue [ 5 ] and Sutter [ 6 ] found that the physical wellbeing and mental health of children with disabilities was impaired due to the reduced availability of rehabilitative services and worsening of the caregivers’ mental health. For example, Dhiman [ 7 ] and Varengue [ 5 ] showed that the pandemic increased the stress, depression and the perception of stress on caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working at home and living with preschool-aged children has particularly influenced the extent of mental distress during the pandemic [ 42 , 43 ]. Therefore, the impact of lockdowns implemented in response to COVID-19 on mental health has raised concerns [ 44 , 45 ]. There is increasing empirical evidence underpinning the negative effects of the pandemic and the associated containment measures on the psychosocial well-being of children [ 33 , 34 , 46 ] and their parents [ 38 , 39 ] in the general population.…”
Section: Introductionmentioning
confidence: 99%